Using the Precision Medicine Analytical Method to Investigate the Impact of the Aerobic Exercise on the Hypertension for the Middle-Aged Women - Zhou, Wei; Liu, Guangdi; Luo, Jun; Zhang, Tingran; Zhang, Le (Bioinformatics Research and Applications, 2017)
The purpose of the study is to investigate why acute aerobic exercise will cause the difference of ambulatory blood pressure for middle-aged women at different time. (1) Methods: There are fifteen middle-aged women volunteered for the study. Each participant receives three experimental interventions: (1) a non-exercise control trail; (2) at 06:30 am and (3) 16:30 p.m. 30 min of aerobic exercise with the mean exercise intensity at 60% of heart rate reserve. The experimental order is random and each participant will wear an automated ABP device to monitor the ABP and heart rate changes for 24 h; (2) Results: The systolic blood pressure, diabolic blood pressure, mean arterial pressure after aerobic exercise in the afternoon as well as the daytime DBP and daytime MAP is significantly lower than the systolic blood pressure, DBP and MAP after aerobic exercise in the morning and non-exercise control trail. Especially, systolic blood pressure can continually reduce for 2 h after acute aerobic exercise in the afternoon; and (3) Conclusion: Aerobic exercise in the afternoon can inhibit the rise of 24 h-ABP and morning blood pressure significantly, which can decrease the incidence of cerebrovascular and cardiovascular events.